2010
DOI: 10.1007/s11284-010-0791-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of herbivores and humans on the Sand Forest species of Maputaland, northern KwaZulu‐Natal, South Africa

Abstract: (194 words)Sand Forest in the Maputaland region of KwaZulu-Natal in South Africa is deemed the most valuable, but also probably the most complex vegetation type of this part of the Maputaland-Pondoland-Albany hotspot of biodiversity. However, Sand Forest is under threat from the current human population growth in that region as well as uncontrolled increases in animal numbers in conservation areas. In this study the impacts of herbivores and humans on the state of woody resources at two sites under differing u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…3;2014 than a year in terms of canopy volume removal (defoliation), observed levels of use are close to levels measured elsewhere that were followed by a retrogression sequence with significant associated vegetation changes. As elephant impact is also considered significant in Tembe (Gaugris & van Rooyen, 2011;Gaugris et al, 2012), a clear danger exists of forcing Tembe's vegetation into a phase of rapid changes. Subsequent to the present study field work in 2004, larger carnivores (Lions and wild dogs) were reintroduced in Tembe, which should be a key step to restore natural limits to herbivore populations' growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3;2014 than a year in terms of canopy volume removal (defoliation), observed levels of use are close to levels measured elsewhere that were followed by a retrogression sequence with significant associated vegetation changes. As elephant impact is also considered significant in Tembe (Gaugris & van Rooyen, 2011;Gaugris et al, 2012), a clear danger exists of forcing Tembe's vegetation into a phase of rapid changes. Subsequent to the present study field work in 2004, larger carnivores (Lions and wild dogs) were reintroduced in Tembe, which should be a key step to restore natural limits to herbivore populations' growth.…”
Section: Resultsmentioning
confidence: 99%
“…6, No. 3;2014 Plants were assigned to one of eight height classes (< 0.1 m, 0.1 to < 0.5 m, 0.5 to < 1.5 m, 1.5 to < 3.0 m, 3.0 to < 5.0 m, 5.0 to < 8.0 m, 8.0 to < 12 m, ≥ 12 m) representative of vegetation structure (Gaugris & van Rooyen, 2011 The range of height classes available to an agent was all height classes where any utilisation event was documented for that agent during our study. It was calculated as the sum of height classes for all woody species with potential for use per vegetation unit for the agent.…”
Section: Discussionmentioning
confidence: 99%
“…A C C E P T E D M A N U S C R I P T Additionally, a study by Gaugris and Van Rooyen (2011), which investigated the effects of herbivores and humans on Sand Forest, indicated that within the sites under observation the effects of fire and climatic changes did not feature in the disturbance of Sand Forest. The disturbances within the Tembe Elephant Park and in the neighbouring Manqakulane rural community were attributed to herbivores and anthropogenic causes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Tembe Elephant Park contains the largest protected sand forest habitat remaining in South Africa (Mucina & Rutherford, ). Sand forest is a restricted range vegetation that includes many endemics (Gaugris & Van Rooyen, ), and is the optimum habitat of suni antelope (Belton, Dalerum & Van Rensburg, ).…”
Section: Introductionmentioning
confidence: 97%